Decreased Exosomal Acetylcholinesterase Activity in the Plasma of Patients With Parkinson’s Disease - Shim, Kyu Hwan; Go, Han Gyeol; Bae, Heewon; Jeong, Da-Eun; Kim, Danyeong; Youn, Young Chul; Kim, SangYun; An, Seong Soo A.; Kang, Min Ju (Frontiers in Aging Neuroscience, 2021)
Exosomes, which are small extracellular vesicles produced from various cell types, contain a variety of molecular constituents, such as proteins, lipids, and RNA. Recently, exosomal biomarkers have been investigated to probe the understanding and diagnosis of neurodegenerative disorders. Previous reports have demonstrated increased exosomal α-synuclein (α-syn) in patients with Parkinson’s disease (PD) in comparison to healthy controls (HC). Interestingly, the cholinergic loss was revealed in the central and peripheral nervous systems in histopathology and molecular neuroimaging. Thereby, we simultaneously examined acetylcholinesterase (AChE) with α-syn as exosomal markers. Exosomes were isolated from the plasma of 34 FP-CIT PET proven patients with PD and 29 HC. Exosomal α-syn and AChE activity were quantified andthe relationship with clinical parameters was analyzed. Remarkably, exosomal AChE activity was significantly decreased in PD compared to HC (P = 0.002). Moreover, exosomal AChE activity in PD revealed a strong negative correlation with disease severity, including H&Y (P = 0.007) and UPDRS part III (P = 0.047) scores. By contrast, no significant difference in exosomal α-syn concentration was observed between groups. These results support the occurrence of cholinergic dysfunction in PD, and they could be implicated with disease progression, especially motor deficits. Exosomal AChE activity with advanced exosome isolation techniques may be a reliable biomarker for the early diagnosis and prognosis of PD.